1999
DOI: 10.1021/jm980602h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four 64Cu-Labeled Somatostatin Analogues in Vitro and in a Tumor-Bearing Rat Model:  Evaluation of New Derivatives for Positron Emission Tomography Imaging and Targeted Radiotherapy

Abstract: Previous studies have shown that modification of the somatostatin analogue octreotide (OC), by substitution of tyrosine for phenylalanine at position 3 and of a C-terminal carboxylic acid for an alcohol, to give Tyr3-octreotate (Y3-TATE) improved uptake of the peptide in somatostatin receptor-positive tissues. To determine which substitution best accounts for increased target tissue uptake, the peptides containing single modifications, Tyr3-octreotide (Y3-OC) and octreotate (TATE), were synthesized. These pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 17 publications
5
78
0
Order By: Relevance
“…In the current study we report lower target tissue uptake and greater nontarget organ uptake than was found previously (1). The CA20948 rat pancreatic carcinoma model uses older rats than required for AR42J tumors (1,37). Immature rats may metabolize 64 Cu-TETA-Y3-TATE differently from older rats, resulting in the observed differences in biodistribution.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the current study we report lower target tissue uptake and greater nontarget organ uptake than was found previously (1). The CA20948 rat pancreatic carcinoma model uses older rats than required for AR42J tumors (1,37). Immature rats may metabolize 64 Cu-TETA-Y3-TATE differently from older rats, resulting in the observed differences in biodistribution.…”
Section: Discussionsupporting
confidence: 49%
“…Modifications to octreotide, a somatostatin analogue, have been evaluated to improve target tissue uptake in somatostatin receptor subtype 2 (SSTr2)-positive tissues; based on these, the octapeptide Tyr 3 -octreotate (Y3-TATE) was identified (1,2). Radiolabeled somatostatin analogues incorporating positron-emitting radionuclides such as 64 Cu and 68 Ga have been shown to be equivalent or improved SSTr2 tracers for positron emission tomography (PET) imaging of SSTr2-positive tumors compared with 111 Inlabeled somatostatin analogues for ␥ scintigraphy (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we compare two 64 Cu radiopharmaceuticals, 64 Cu-TETA-Y3-TATE ( 64 Cu- [1]) and 64 Cu-CB-TE2A-Y3-TATE ( 64 Cu- [2]). Y3-TATE-based radiopharmaceuticals are highly specific for SSTr2, have a higher affinity (typically, IC 50 , 2 nM (19)), and are more rapidly internalized into cells expressing this receptor than octreotide-based analogs (6,20). 64 Cu-[1] demonstrated higher uptake into tumor and other somatostatin-receptor-rich tissues than 64 Cu-TETAoctreotide in CA20948 tumor-bearing rats and AR42J tumor-bearing severe combined immunodeficiency (SCID) mice (21).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It has been demonstrated that with somatostatin-based peptides, changing the C-terminus from an alcohol (OC) to a carboxylic acid (TATE) increases uptake of these peptides in receptor-rich tissues. 18,23,28 This can result in a higher dose to the tumor, while not dramatically affecting the absorbed doses to normal tissue. 18 As a consequence, the most recent developments in the use of radiolabeled somatostatin analogs have focused on the use of the TATE derivative.…”
Section: Discussionmentioning
confidence: 99%